Penurunan Konsentrasi BOD Limbah Domestik Menggunakan Sistem Wetland dengan Tanaman Hias Bintang Air (Cyperus alternifolius) - Hasti Suprihatin (Universitas Riau, 2014)
Domestic waste water is the highest contributor of the pollution at this time,because the waste which discharged into the stream is not being processed first, but it directlydischarged into the stream. In the big amount of waste, some microorganisms in the stream isno longer able to decompose contaminants that exist. The purpose of this study to determinewhether the wetland that contains Cyperus alternifolius can decompose the organic content ofBOD in domestic waste.The research method is using observation and measurement of theparameters BOD by using wetland which contain of Cyperus alternifolius with ArtificialWetland Subsurface Flow System (SSF-Wetlands).Results of laboratory tests of domesticwaste after processed by wetland can reduce the organic content of the BOD is 1632.0 mg/l to9 mg/l. Artificial Wetland System Subsurface Flow (SSF-Wetland) by using plants of watercan reduce the concentration of BOD in domestic waste. To get the quality of domestic wastein accordance with the quality standard, the required optimum residence time for 4 days.